If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6z=39-2z
We move all terms to the left:
6z-(39-2z)=0
We add all the numbers together, and all the variables
6z-(-2z+39)=0
We get rid of parentheses
6z+2z-39=0
We add all the numbers together, and all the variables
8z-39=0
We move all terms containing z to the left, all other terms to the right
8z=39
z=39/8
z=4+7/8
| 14*6=3*n | | 8x+21=3÷11 | | (x+2)(x-9)=(7x+17) | | 8x+21=3/11 | | 5(y-1)+16(2y+3)=3(2y-7) | | 10*62=n*6.2 | | y=-9-4-9 | | 0*53=n*34 | | 3(4x+1)=6x+2 | | n/5.9=11 | | 2x+8-x=3x-12 | | 9.8x=63.7 | | -5x=10-15. | | 28*n=7*12 | | 5x=10-15. | | (-6d=2)-(7=2d) | | 36*n=36 | | p/1.2=25/15 | | 17/15+s/15=-4 | | 18+30=6(2x-1) | | 13+4K=13+5k | | -67b+6=9b+43 | | 1=8x-6=2=7x | | 8p-8=6(-7p+7) | | 5x-81=360 | | 63-x=2x=3 | | (7x^2-27)=(6x^2-6x) | | 4(m-4)-6=-31-5m | | 9^2-18=8^2-7x | | 18-2|c+7|=12 | | -42v+33=8v | | (9x-18)=(8x-7x) |